Public-Sector Employment in an Equilibrium Search and Matching Model - James Albrecht; Monica Robayo-Abril; Susan Vroman (Institute of Labor Economics (IZA), 2017)
We extend the Diamond-Mortensen-Pissarides model of equilibrium unemployment to incorporate public-sector employment. We calibrate our model to Colombian data and analyze the effects of public-sector wage and employment policy on the unemployment rate, on the division of employment between the private and public sectors, and on the distributions of wages in the two sectors.
Keywords: J45; J64; D83; 330; public sector; search and matching; wages; unemployment